2017
DOI: 10.1590/s0102-865020170090000009
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic mesenchymal stem cells and xenogenic platelet rich plasma, associated or not, in the repair of bone failures in rabbits with secondary osteoporosis

Abstract: Allogeneic mesenchymal stem cells and xenogenic platelet rich plasma, associated or not, in the repair of bone failures in rabbits with secondary osteoporosis¹ 9-Experimental SurgeryActa Cir Bras. 2017;32(9):767-780 AbstractPurpose: To assess the efficacy of allogeneic mesenchymal stem cells and xenogenic platelet rich plasma in the treatment of bone failure of osteoporotic rabbits secondary to estrogenic deprivation and iatrogenic hypercortisolism. Methods: Eight female rabbits underwent ovarian resection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 19 publications
4
22
0
2
Order By: Relevance
“…Risk of bias of animal studies was high for almost all the examined studies. Among the 13 included in vivo studies, three for PLT functions during OP and 10 for PLT derivatives in OP, 10 of them have not declared the method of sequence generation [41,42,[49][50][51][52][53]56,57], in one study the method was unclear [55] and in the remaining two studies the method of sequence generation was clearly declared [40,58]. The majority (n = 7) of the studies showed that groups were similar concerning baseline characteristics (i.e., age, weight, sex) and two studies showed that allocation was adequately concealed [40,58].…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…Risk of bias of animal studies was high for almost all the examined studies. Among the 13 included in vivo studies, three for PLT functions during OP and 10 for PLT derivatives in OP, 10 of them have not declared the method of sequence generation [41,42,[49][50][51][52][53]56,57], in one study the method was unclear [55] and in the remaining two studies the method of sequence generation was clearly declared [40,58]. The majority (n = 7) of the studies showed that groups were similar concerning baseline characteristics (i.e., age, weight, sex) and two studies showed that allocation was adequately concealed [40,58].…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
“…All 10 articles on PLT derivatives in OP were about vivo or both in vivo and in vitro studies. With the exception of the study by Rocha et al [56] that used rabbits submitted to elective ovariosalpingohysterectomy as OP animal model all the other studies employed ovariectomized (OVX) mice and rats to induce OP ( Table 3). All studies used PRP as PLT products with the exception of a study which used L-PRF [58].…”
Section: Platelet Derivatives In Osteoporosismentioning
confidence: 99%
See 2 more Smart Citations
“…Більшість наукових робіт, що порівнюють між собою результати застосування кортикостероїдів та збагаченої тромбоцитами плазми, мають клінічну спрямованість, саме тому актуальним є проведення експериментального біологічного дослідження, яке дало б змогу виявити та порівняти особливості структурних змін, що виникають у травмованому ахіловому сухожиллі за умов застосування обох лікувальних засобів. Слід зауважити, що через важкість отримання від дрібних лабораторних тварин адекватної для проведення досліду дози крові в експериментах поряд із аутологічною PRP використовують і ксеногенну [6,7].…”
Section: вступunclassified